World social protection report 2014/15 : building economic recovery, inclusive development and social justice - International Labour Office (Geneva : ILO, 2014)
Social protection policies play a critical role in realizing the human right to social security for all, reducing poverty and inequality, and promoting inclusive growth - by boosting human capital and productivity, and by supporting domestic demand and structural transformation of national economies. This ILO flagship report provides a global overview of the organization of social protection systems, their coverage and benefits, as well as public expenditures on social protection. The report follows a life-cycle approach, starting with social protection for children, followed by schemes for women and men in working age, and closing with pensions and other support for older persons. It also assesses progress towards universal coverage in health. The report further analyses trends and recent policies, such as the negative impacts of fiscal consolidation and adjustment measures, and urgently calls to expand social protection for crisis recovery, inclusive development and social justice. The World Social Protection Report 2014/15 includes valuable and comprehensive statistical annexes with the latest social protection data.
Introduction -- Social protection for children and families -- Social protection for women and men of working age -- Social protection for older women and men: pensions and other non-health benefits -- Towards universal coverage in health -- Expanding social protection: key to crisis recovery, inclusive development and social justice.
Includes bibliographical references (p. 315-335).
Keywords: Social security; Social justice; Social policy; Family policy; Old age pensions; Health insurance